2024 IFPRI A-133 (Uniform guide) - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
We have audited the financial statements of International Food Policy Research Institute (IFPRI), which comprise the statements of financial position as of December 31, 2024 and 2023, the related statements of activities, functional expenses, changes in net assets and cash flows for the years then ended, and the related notes to the financial statements.